CRIMINAL OFFENSIVE AGAINST CHILDREN DURING THE 2019 CORONAVIRUS DISEASE PANDEMIC (COVID-19) - Prajna Sherina Paramita; Mas Anienda Tien (JOSAR (Journal of Students Academic Research), 2022)
The purpose of the study was to examine what factors caused an increase in cases of child sexual abuse during the COVID-19 pandemic at Polrestabes Surabaya, then to determine the role of the Police in overcoming the crime of child molestation and to find out the efforts that the Police can take against the obstacles that arise. faced due to the COVID-19 pandemic. The research method in this thesis is empirical juridical, data collection in this research is carried out by means of interviews, observations and literature studies. Data analysis used descriptive analytical method and used a qualitative approach. The results of this study showed that the factors that caused the crime of sexual abuse against children continued to increase during the covid-19 pandemic due to government policy factors, economic factors, family factors, but the Police had given the best to children but due to the covid-19 pandemic. There are still obstacles in overcoming the victims of the crime of obscenity, there are three obstacles in overcoming cases of child abuse. The first factor is the lack of supporting evidence or witnesses in a case reported by the victim. Factors Both the victim or the victim's family do not want to make a fuss about the case. The third factor of the perpetrators is unknown. Thus, from these obstacles, there are efforts made by the Police, namely pre-emptive efforts, preventive efforts, and preventive efforts to tackle criminal acts of sexual abuse against children. Keywords: : Crime of Obscenity, Children, Covid – 19